MEMBELAJARKAN KESENIAN INDANG DALAM MEMAJUKAN KREATIVITAS REMAJA BISATI SUNGAI SARIK (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the process of teaching Indang Art in developing the creativity of teenagers in Nagari Bisati Sungai Sarik, VII Koto District, Padang Pariaman Regency. This study uses a qualitative method with a descriptive approach. The research instrument is the researcher themselves, assisted with stationery and a camera. Data is collected through observation, in-depth interviews, literature studies, and documentation. The research informants include Indang art enthusiasts, trainers, and teenagers who actively participate in traditional art activities in Nagari Bisati Sungai Sarik. The steps in analyzing the data include data reduction, data presentation, and drawing conclusions. The research results show that the process of teaching Indang Art not only focuses on mastering movement techniques and rapa’i playing, but also serves as a medium for developing creativity and character in teenagers. Teenagers’ creativity grows through involvement in various traditional art activities like Randai and Gandang Tambua. In addition, learning Indang shapes character traits such as discipline, self-confidence, respect, and social cooperation. Indang Art has proven to be a means of cultural preservation as well as an effective non-formal educational medium for teenagers amid the development of modern culture. Therefore, the Indang learning model in Bisati can be used as a prototype for preserving traditional arts in other regions, where active participation from community leaders and providing creative space for the youth are key to sustaining a cultural identity.